On the Verge of the Next EU Enlargement. Accession Legal Framework: Conceptual Overview - Sylwia Katarzyna Mazur (Croatian Yearbook of European Law and Policy, 2024)
Since the founding days of the European Coal and Steel Community, the European integration model has been designed as an open one. Therefore, the enlargement of the European Union from its six founding members to its current twenty-seven is considered not only a success story for the EU but for Europe as a whole. Enlargement, as a twofold process, requires adequate preparation by the acceding State and the EU’s capacity to integrate the new member. Despite the transformative power of European integration (where even the prospect of membership can trigger significant reforms), the process is governed by the relatively concise Article 49 of the Treaty on European Union (TEU), which has evolved significantly in practice. The purpose of this paper is threefold. Firstly, it will elucidate the evolving character of the accession procedure. Secondly, it will analyse the balancing act between the increasing complexity of the process and the mechanisms of pre-accession assistance combined with flexibility measures. Thirdly, it will explore the role and significance of political will throughout the entire accession process.